Internet addiction and online impulsive buying among university students: A cross-sectional study with regression and bootstrapped mediation - Yanuar Fahrizal; Lia Silvia; Andi Buanasari (Jurnal Keperawatan Padjadjaran, 2026)
Background: University students frequently experience psychological distress. With the internet embedded in daily life, online activities, including online shopping may be used as coping strategies, but excessive use can contribute to internet addiction. Mechanism-oriented research also suggests that general online exposure may influence online impulsive buying through proximal processes such as internet addiction. Purpose: This study aimed to determine factors associated with internet addiction among university students and to test whether internet addiction mediates the association between general online exposure (hours/day) and online impulsive buying. Methods: A quantitative cross-sectional design was used among 386 university students at a campus in Kasihan, Bantul, Yogyakarta, Indonesia (January-April 2024) using convenience sampling. Internet addiction was measured using the Indonesian Internet Addiction Test (IAT) validated by Siste et al. (2021) (18 items; three-factor structure; Cronbach’s α=0.855). Online impulsive buying was measured using the Impulse Buying Tendency Scale (IBTS) adapted to online context. Psychological distress was measured using the Depression Anxiety Stress Scale (DASS-42). Spearman correlations were used for bivariate analysis. Multiple linear regression identified predictors of internet addiction. A simple mediation model (PROCESS Model 4; 5,000 bootstrap samples) tested Duration → internet addiction → online impulsive buying, controlling for age, sex, DASS total, and online loan history. Results: Mean internet addiction score was 40.57 (SD 13.86) and mean online impulsive buying score was 37.02 (SD 8.91). Internet addiction correlated significantly with online impulsive buying (ρ=.369, p<.001), depression (ρ=.163, p=.001), anxiety (ρ=.131, p=.010), stress (ρ=.147, p=.004), and Duration (ρ=.131, p=.010). In multivariable regression, online impulsive buying (B=0.673, p<.001) and stress (B=0.210, p=.002) were significant predictors of internet addiction (R²=.215). In mediation analysis, the indirect effect of duration on online impulsive buying through internet addiction was significant (ab=0.1006, 95% bootstrap CI [0.0085, 0.2154]), consistent with an indirect-only mediation pattern. Conclusions: Online impulsive buying and stress were significantly associated with internet addiction, with online impulsive buying as the strongest predictor. Internet addiction also mediated the association between general online exposure and online impulsive buying.